KOMPARASI SARANA. PRASARANA, TATA RUANG DAN AKSESIBILITAS DINAS PERPUSTAKAAN DAN KEARSIPAN DAERAH JAWA BARAT DAN DINAS ARSIP PERPUSTAKAAN KOTA BANDUNG - Nur Khofifah, Eriska; Alya Rasidi, Putri; Inten Legi Novita Sarip, Ajeng (UPT Perpustakaan Universitas Bengkulu, 2025)
Research regarding comparisons of facilities, infrastructure, spatial planning and accessibility is also important as evaluation and reference material for improving library services in the future. Library facilities and infrastructure are the main aspects that determine the comfort and completeness of the services that can be provided to visitors. First, there are significant differences between the facilities and infrastructure available in the two library objects. The Bandung City Library has more facilities such as multimedia rooms and meeting halls, while the West Java Library focuses more on book collections and reading rooms. This difference certainly affects the activities that can be carried out in the library. Second, in terms of spatial layout, the two library objects have different designs. The Bandung City Library has a modern and open design with lots of windows and natural lighting, while the West Java Library still has traditional elements with the use of thick walls and artificial lighting. This also affects visitor comfort and the learning atmosphere in the library. Third, accessibility is also an important factor in choosing a library. The Bandung City Library is more easily accessible because it is located in the city center and can be reached by public transportation, while the West Java Library is located in a suburban area. This can influence the number of visitors and community participation in library activities. The method used in this research is a qualitative method. The qualitative research method is a research method used to examine the natural state of objects, where the researcher is the main tool, data collection techniques are carried out through cross-examination, data analysis is inductive and the results of qualitative research emphasize significance rather than generalization.